Efeitos das condições neuromotoras da paralisia cerebral no sentido háptico durante tarefas de controle postural - Costa, Thais Delamuta Ayres da [UNESP] (2014)
Atypical motor development in cerebral palsy individuals causes several and complex motor disorders, including deficits in the postural control. An efficient postural control relies on muscle and joint functional activity, as well as on efficiency of sensory systems (the visual, vestibular and somatosensory). In addition, the haptic touch, a haptic subsystem of system is involved in the activities of manual manipulation, allowing the exploitation of the properties of the object and consequently the orientation and positioning of the body parts and body as a whole in space. Several studies emphasized the contribution of haptic input to postural control rising from the handling of rigid and non-rigid tools. The haptic use of non-rigid tools during postural control tasks is illustrated in the anchor system paradigm, proposed by MauerbergdeCastro (2004). In this paradigm, the maintenance of stability via haptic information is gathered during the handling of flexible cables attached to loads resting on the floor. Studies using this anchor system paradigm demonstrated its effectiveness in stabilizing posture in several groups: young adults, children, older individuals, and intellectually disabled. Therefore, the present study aimed to examine whether neuromotor impairment in postural control of cerebral palsy would be compensated by the integration of haptic information, anchor system, simultaneously achieving postural tasks. Twenty individuals with cerebral palsy (spastic hemiparetic, diparetic and ataxic) are required to stand on a force platform in the following conditions: 1) holding anchors with full vision, 2) holding anchors without vision, 3) without the anchors with full vision, 4) without the anchors and without vision. These conditions include two contact surfaces: direct contact with the force platform surface (estable) and foam padded surface placed on the force platform. Flexible cables of the anchor system were attached to load...